Differential response of selected bread wheat (Triticum aestivum L.) genotypes for salt tolerance by using multiple parameters - Singh, Sanjay; Sengar, Rakesh Singh; Kulshreshta, Neeraj (Journal of Cereal Research, 2016)
The aim of the present study was to identify new sources of salt tolerance on the basis of relative performance of multiple parameters with respect to salt tolerance indices at 10.0 dSm-1 in wheat. Ten bread wheat genotypes were evaluated in pots following completely randomised design for salinity tolerance (ECiw=10.0 dSm-1) imposed 21 days after sowing (S1) and at the time of sowing (S2). In the present study Kharchia65, UP1109 and K9423 were found to be the most tolerant while HD2009 and AKAW4627 were salt sensitive among studied genotypes according to cluster analysis based on relative salt tolerance indices of multiple parameters. The differences among genotypes of bread wheat reflected important genetic variability under salinity, which can be further explored and used for the wheat breeding programs. Cluster analysis with multiple agronomic parameters simultaneously can facilitate rankings of salt tolerance of wheat genotypes.